HAMKA's Thoughts on the Integration of Islamic Values and Indonesian Nationalism - Erwin, Erwin; Ermagusti, Ermagusti; Putra, Rido; Tri Hadi, Rahmad (University of Darussalam Gontor, Indonesia, 2024)
The article focuses on the integration of Islamic values and Indonesian nationalism as interpreted by Hamka. In contemporary Indonesian society, there is a recurring tension between religious values and national identity, often resulting in societal discord and fragmented national unity. The purpose of this study is to analyze and elucidate Hamka’s perspectives on the harmonization of Islamic teachings and Indonesian nationalism. By examining Hamka’s works and thoughts, the study aims to provide a comprehensive understanding of how Islamic values can coexist and support the principles of Indonesian nationalism. The method used in this research is a descriptive-analytical method with an integration and interconnection approach. The primary data used in this research are Hamka's works. At the same time, the secondary data in this research are books, journal articles, and other websites that discuss Hamka's thoughts. The results showed that in applying and integrating Islamic values in the frame of nationality and Indonesianness, Hamka divided it into three main thoughts. First, Islam and the vision of humanity. The vision of Islam is a religion for all mankind and humanity and religion for the next generation, so that religious da'wah is sustainable, renewed, and emphasized to oneself the family, and society; Second, nationality and freedom. The spirit of nationality arises from true faith and does not break away from the roots of